Curriculum theory: Empowering teachers in delivering effective teaching for children’s holistic development - Idowu Tope Aisha Adekanbi; Michael Timilehin Oladele (Curricula)
The significance of curriculum in education cannot be underestimated, as it enables teachers to know what to teach during teaching and learning. The dominant curriculum used in schools today is a scripted curriculum that does not allow teachers to see learners as co-creators in constructing knowledge. Many teachers find it challenging to adjust this curriculum to the interests and abilities of learners. This article aims to explore how scripted curricula can be adapted in childhood education to promote a child-centered approach that acknowledges children's knowledge, interests, needs, and abilities. This article examines 2011 to 2024 peer-reviewed articles that emphasize curriculum flexibility and students’ involvement in creating knowledge with 104 articles. The findings show that teachers need the knowledge of curriculum theory to modify and implement scripted curriculum in a way that is inclusive and culturally responsive to all learners. This knowledge will enable teachers to deliver instruction capable of motivating learners to work at their own pace and participate in meaningful and rewarding learning experiences.